Building the Future of Education with Independent Learning Curriculum Innovation in the Society 5.0 Era - Haliwigena, Sarah; Kamil, Mustofa; Wahyudin, Uyu; Ardiwinata, Jajat S. (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to analyze the innovation of the independent learning curriculum in the era of society 5.0 in building the future of education. The research method used is a qualitative approach to literature studies that focuses on understanding meaning and does not rely on mathematical or statistical evidence. The data collection technique was carried out through a literature review that discussed the innovation of the independent learning curriculum in the era of society 5.0 in building the future of education sourced from relevant journals and books. This method allows researchers to gain in-depth insight into the innovation of the Independent Learning Curriculum in the Society 5.0 Era in the context of education. The result of this work, namely the Independent Learning curriculum in the Society 5.0 era, produces a positive impact by prioritizing mastery of various fields of science without the limitations of study programs, increasing students' flexibility to explore individual interests, and strengthening critical skills and independence in the face of complex changes. This curriculum also pays attention to students' identities as agents of change who are responsible, ethical, and contribute positively, as well as broadening perspectives through exploring knowledge to face future challenges with strong competence.